The effect of Gauze Dressing use on reduction of Oronasal Fistula Rates following Cleft Palate Repair - Fatma Bilgen; Alper Ural; Mehmet Bekerecioğlu (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2019)
Background: The most incident and the most persistent complication following cleft palate repair is oronasal fistula. Fistulas involving the soft palate may be corrected via excision and primary closure; however fistulas of the hard palate constitue a majör challange.  Aims: In this study, in order to reduce the rate of oronasal fistula following cleft palate surgery, we present postoperative use of palatal gauze dressing.  Patients and Methods: The patients were enrolled randomly into two groups as Group one and two. For group two patients, at the end of operation, an antibiotic pomade absorbed sterile gauze was fixed at the palate with 2/0 silk sutures, under moderate pressure in order not to interfere with flap circulation.  Results: Of the 7 fistulas in group one, 5 were located on the hard palate and 2 on the soft palate, whereas in, 2 were located on the hard and two on the soft palate. No other complications were encountered.  Conclusion: The use of an antibiotic pomade-absorbed palatal gauze, tight adherence of palatal flaps to the underlying bone is achieved. Besides, serving as a barrier, the gauze prevents infection with food remnants and irritation with foreign bodies.